Monitoring the acclimatization of a Chlorella sp. From freshwater to hypersalinity using photosynthetic parameters of pulse amplitude modulated fluorometry. (August 2020) - Anandraj, Akash; White, Sarah; Naidoo, Devashan; Mutanda, Taurai
Highlights: Contamination of raceway ponds severely impedes commercial microalgal cultivation. A freshwater Chlorella sp. was successfully acclimatized to a saline environment. PAM fluorometry investigated the physiological changes involved in acclimatization. Acclimation of algae to saline conditions may limit contamination of raceway ponds. Abstract: Contamination of freshwater raceway ponds impedes the commercial cultivation of microalgae. Acclimatization of freshwater microalgae to hypersaline conditions offers a means to reduce contamination. A freshwater Chlorella species was cultured in a gradient of salinities ranging from 5 to 40‰ and pulse amplitude modulated fluorometry recorded photosynthetic functioning. While the average salinity of seawater is 35‰, optimum acclimatization occurred at 20‰, at which point the growth rate (1.6 µg chl a L −1 d −1 ) was not significantly different from the control (1.8 µg chl a L −1 d −1 ). The maximum relative electron transfer rate was lower (9 to 12 µmol m −2 s −1 ) at 5 to 20‰ as compared to 40‰ (28 µmol m −2 s −1 ) where no algal growth was recorded. ATP and NADPH were thus shunted towards synthesis of molecules that offset cytoplasmic osmotic stress. Culturing this Chlorella strain in raceway ponds under saline conditions may reduce contamination and improve productivity.